A Study of Nail Changes in Various Dermatosis - Karim, ATM Rezaul; Sadeque, Shayesta Parvin; Khan, Md Abdul Latif; Hasan, Md Sayeed; Al Azad, Md Abdus Samad; Siraj, Md Shajahan; Kabir, Md Humayun; Begum, Syeda Tania (Journal of Armed Forces Medical College, Bangladesh, 2016)
Introduction: Nails act as a window to diagnosis of skin diseases. Various dermatosis affect the nails and the severity of the skin disorder is reflected in the nails. Nail changes are seen in various dermatosis like psoriasis, lichen planus, onychomycosis, collagen vascular disorders, vescicobullous disorders and other papulosquamous disorders. Objectives: The objective of this study is to see the abnormal nail changes in patients reporting to the Department of Dermatology and Venereology in Combined Military Hospital, Comilla. Materials and Methods: This is a prospective study, carried out in the department of Dermatology and Venereology, Combined Military Hospital, Comilla from January 2014 to December 2014. Total 250 patients based on nail changes coming for various dermatological conditions were enrolled in this study. A detailed clinical history regarding onset, duration and associated symptoms was asked. A thorough systemic and dermatological examination was conducted and all details were recorded on a special proforma. Routine investigations like haemoglobin concentration (Hb), total leucocyte count (TLC), differential leucocyte count (DLC), ESR, platelet count, urine routine examination, serum urea and creatinine were carried out to confirm the diagnosis. Special investigations like nail clipping for bacteriological and fungal infection and skin biopsy were carried out whenever required. Results: This study showed, out of 250 patients, nail changes were seen in various dermatosis. Maximum number of patients (50%), were of onychomycosis (Fig-1) followed by 12% patients of paronychia (Fig-2), eight percent patients of Psoriasis (Fig-3), eight percent patients of lichen planus (Fig-4) and four percent patient were of Twenty nail dystrophy(Fig-5). Out of 20 patients of psoriasis the most common changes were pitting, subungual hyperkeratosis, onycholysis and discoloration. Out of 20 cases of lichen planus, the most common changes were longitudinal ridging, pterygiumand onycholysis. Twenty nail dystrophy was seen in 10 cases and the commonest cause of twenty nail dystrophy was idiopathic in 40% cases, psoriasis in 30% cases, lichen planus in 20% cases and alopecia areata was seen in 10% cases. Conclusion: A variety of nail changes can occur in various dermatological, systemic and other conditions. The nail unit is capable of only a limited number of reaction patterns; therefore, many diseases share similar changes, but correlation of the nail changes helps dermatologist to reach conclusive diagnosis. Nails remain an under studied and yet quiet accessible structure that lends itself for examination and evaluation. Hence truly said that nails are the windows through which one can look into the health of the patient. Journal of Armed Forces Medical College Bangladesh Vol.11(1) 2015: 38-44